1982
DOI: 10.2535/ofaj1936.58.4-6_837
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Studies on a Vitamin A-Storing Cell and its Complex with Macrophage Observed in Mouse Pancreatic Tissues following Excess Vitamin A Administration

Abstract: Summary : In this experiment, mouse pancreatic connective tissues were examined following excess vitamin A administration, and a new cell type and a new cell complex were found.In the normal state, several cell species and structures are observed in the intralobular and interlobular connective tissues such as fibroblasts, fixed macrophages (one of mononuclear phagocytes), blood capilleries with pericytes, secretory ducts, myelinated or unmyelinated nerve fibers and collagenous fibers. On the other hand, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 6 publications
1
67
0
3
Order By: Relevance
“…Vitamin A storing cells in the pancreas were originally observed in 1982 in mice fed an excess of this vitamin 12 but these cells were first described in the human pancreas eight years later. 13 A potential role of this cell system in pancreatic fibrogenesis was suggested via isolation of myofibroblast-like cells from the human pancreas, 14 and it has been demonstrated that vitamin A storing cells from pancreas can in fact differentiate in primary culture into myofibroblasts producing extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A storing cells in the pancreas were originally observed in 1982 in mice fed an excess of this vitamin 12 but these cells were first described in the human pancreas eight years later. 13 A potential role of this cell system in pancreatic fibrogenesis was suggested via isolation of myofibroblast-like cells from the human pancreas, 14 and it has been demonstrated that vitamin A storing cells from pancreas can in fact differentiate in primary culture into myofibroblasts producing extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PSCs were first identified as fat-storing cells in the pancreas of vitamin A-loaded mice 1 and were subsequently identified in normal rat and human pancreatic tissue 2 from which they can be isolated and expanded by in vitro culture. 3,4 Under normal conditions, PSCs are quiescent and are characterized by cytoplasmic lipid droplets rich in vitamin A.…”
Section: Introductionmentioning
confidence: 99%
“…Research efforts in elucidating the mechanisms of alcoholic pancreatic fi brosis were given signifi cant impetus with the identifi cation, isolation and characterization of stellate cells in the pancreas [73][74][75] . PSCs are morphologically similar to hepatic stellate cells, the principal effector cells in liver fi brosis [76] .…”
Section: Pathogenesis Of Alcoholic Pancreatic Fibrosismentioning
confidence: 99%